2019
DOI: 10.14740/cr902
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Hemorrhagic Pericardial and Pleural Effusion in a Patient Receiving Apixaban

Abstract: Direct oral anticoagulants (DOACs) are used for many conditions where anticoagulation is needed such as non-valvular atrial fibrillation, deep vein thrombosis (DVT) and pulmonary embolism (PE). These novel agents have become popular since they do not require monitoring of therapeutic levels and there is a lower risk of certain bleeding complications when compared to warfarin. However, the efficacy and side effect profile of these agents have not been widely studied in certain patient cohorts, namely cancer pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Spontaneous hemorrhagic pericardial effusion has been reported previously after the initiation of factor Xa inhibitors. 7,8 In this case, hemorrhagic conversion of uremic pericarditis while undergoing anticoagulation is also a possibility. Although the efficacy of adexanet alfa in the pericardial bleeding subgroup was not specifically reported in the ANNEXA-4 study, subjects with pericardial bleeding were included in this study.…”
Section: Discussionmentioning
confidence: 97%
“…Spontaneous hemorrhagic pericardial effusion has been reported previously after the initiation of factor Xa inhibitors. 7,8 In this case, hemorrhagic conversion of uremic pericarditis while undergoing anticoagulation is also a possibility. Although the efficacy of adexanet alfa in the pericardial bleeding subgroup was not specifically reported in the ANNEXA-4 study, subjects with pericardial bleeding were included in this study.…”
Section: Discussionmentioning
confidence: 97%
“…Together this draws suspicion towards Rivaroxaban as the PcE-cause. A case series by Cinelli et al (2019) [ 8 ] presents three cases of direct oral anticoagulant (DOAC)-induced PcE in oncologic patients. All three cases showed malignant cells in fluid cytology, suggesting that this may have played a causative role rather than Rivaroxaban.…”
Section: Discussionmentioning
confidence: 99%
“…Atia R et al reported two cases of spontaneous choroidal hemorrhage in patients taking rivaroxaban and dabigatran [32]. Hemorrhagic cardiac tamponade and spontaneous hemopericardium have been reported in patients receiving DOACs [33][34][35]. Jun et al reported three cases of spontaneous vitreous hemorrhage in patients taking rivaroxaban for atrial fibrillation.…”
Section: Epidemiologymentioning
confidence: 99%
“…Cullen's sign-the presence of bruising or edema in the abdominal wall-could indicate an underlying intra-abdominal bleed [75]. Intra-thoracic bleed and pulmonary hemorrhage could present as hemothorax and hemoptysis, respectively [35].…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation